Pengaruh Lokasi dan Promosi Penjualan Terhadap Keputusan Pembelian - Tintin Aininda; Yudhi Koesworodjati (Jurnal Riset Mahasiswa, 2021)
The culinary industry is an industry that has experienced the most significant development in the city of Bandung, where its development is marked by the number of actors trying the culinary business. The growing culinary business makes business actors in this field have to be able to adjust to what consumers want and need in order to make purchases of company products. Location is a factor that determines the success of a business because location is an important factor in determining consumer behavior. In addition to location, sales promotions can also attract new customers, encourage new customers to buy more, give gifts or rewards to existing customers, and prevent consumers from going to other products or services. This study aims to determine the effect of location and sales promotion on purchasing decisions (a survey of consumers at Aditi Coffee House Bandung) simultaneously or partially. The research method used is descriptive and verification method with a total sample of 90 respondents. The data analysis method used is multiple linear regression analysis, multiple correlation and coefficient of determination.